2004
DOI: 10.1300/j006v24n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Prehension in Infants and Children

Abstract: Learning to reach for and manipulate objects requires considerable neuromotor control and flexibility. Through environmental and object exploration individual neuromotor strategies expand, and prehensile skills improve, as infants and children overcome constraints. Infants and children with prehensile deficits often have difficulty exploring objects and the environment, thus, may not sufficiently develop the strategies needed to expand their prehensile skills. This article reviews neuromotor factors that influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 155 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…Both bimanual and unimanual reaching with early strong hand preference at four to six months of age can be considered to be a strong sign of early hemiplegia (Golomb et al, 2001). Studies of infants who have sustained an early perinatal stroke from 4 to 7 months corrected age have suggested that until reach to grasp behaviours have emerged, an asymmetry may not be clearly evident so that a hemiparesis may not be confirmed (Duff and Charles, 2004;Duff and Gordon, 2003).…”
Section: Future Directions 301mentioning
confidence: 99%
“…Both bimanual and unimanual reaching with early strong hand preference at four to six months of age can be considered to be a strong sign of early hemiplegia (Golomb et al, 2001). Studies of infants who have sustained an early perinatal stroke from 4 to 7 months corrected age have suggested that until reach to grasp behaviours have emerged, an asymmetry may not be clearly evident so that a hemiparesis may not be confirmed (Duff and Charles, 2004;Duff and Gordon, 2003).…”
Section: Future Directions 301mentioning
confidence: 99%
“…209 Studies of infants who have sustained an early perinatal stroke from 4 to 7 months corrected age have suggested that until reach to grasp behaviours have emerged, an asymmetry may not be clearly evident so that a hemiparesis may not be confirmed. 186,187 Critical periods of typical upper limb motor development…”
Section: Discussionmentioning
confidence: 99%
“…60 Studies of infants who have sustained an early perinatal stroke before four to seven months corrected age have suggested that until reach to grasp behaviours have emerged, an asymmetry may not be clearly evident and hemiparesis not confirmed. 186,187 Early intervention for infants at risk of developing congenital hemiplegia is considered to be very important, however, standard rehabilitation programs generally commence after six months of age due to delayed detection. A further consideration regarding the timing of commencement of intervention is that important phases of brain reorganisation may have already occurred.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations